PENGEMBANGAN KAWASAN WISATA PANTAI TEMAJUK MEALUI PEMBATASAN SAMPAH PLASTIK - Wulan Purnamasari; Fani Heru Wismono; Uray Juniardi (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
Coastal tourism development activities in Temajuk provide economic benefits to the community around the coast. However, on the other hand, the beach faces a very disturbing problem of plastic waste, plastic waste around Temajuk Beach is mostly contributed by household waste and also garbage from the ocean. Active and collaborative involvement of various parties in helping to limit the use of plastic waste in the Temajuk Beach Area is very much needed. Interviews with stakeholders and literature studies on existing data such as the government and other institutions involved to get quick wins for plastic waste activities in the Temajuk Beach Tourism Area. So based on the mapping of the problems found in the field, a lot of information is then divided into three parts. The first is the problem that occurred, then followed by various solutions to the problem in brief, and the last part is the expectation regarding the handling of waste management in the Temajuk Beach Tourism Area. Based on the mapping, it can be seen that the waste problem that appears in the Temajuk Tourism Area is not only a problem of waste generation, especially plastic waste. However, the problems that arise are related to the overall management of solid waste management which is still not optimally perceived by the community.